Pengalaman Perawat Merawat Pasien ODGJ dengan Covid-19 di RSJ Sambang Lihum - Mohamad Hamsanie; Bahrul Ilmi; Muhamamad Syafwani (Syntax Corporation Indonesia, 2021)
COVID-19 is an infectious disease so special treatment is needed especially in ODGJ patients with COVID-19. The study aims to explore the experience of nurses in treating ODGJ patients with COVID-19. This study aims to explore and get an overview of the experience of nurses in caring for ODGJ patients with COVID-19 at Sambang Lihum Hospital. The method used is qualitative phenomenology with purposive sampling sample selection, with a sample count of 5 participants. The results of the study found 5 main themes, namely the psychological response of nurses in caring for ODGJ patients with COVID-19, the physical response of nurses in using APD level 3, the process of nurse adaptation in caring for ODGJ patients with COVID-19, the behavior of ODGJ patients with COVID-19 when treatment and how to treat ODGJ patients with COVID-19.The results concluded that nurses can adapt in treating ODGJ patients with COVID-19 through coping mechanisms and efforts to maintain immunity. Spiritual strengthening is one of the copings that becomes a counterweight to the physical and psychological health of nurses so that the nurse's experience becomes adaptive. Research advice is to set work patterns so that nurses are not exhausted while working using APD level 3, providing training in using APD level 3 and support facilities and infrastructure to support occupational safety and health from nurses in providing safe services for ODGJ patients with COVID-19.